Advance of genetically modified pigs in xeno-transplantation - Deng, Jiacheng; Yang, Lin; Wang, Ziru; Ouyang, Hongsheng; Yu, Hao; Yuan, Hongming; Pang, Daxin (Frontiers in Cell and Developmental Biology, 2022)
As the human standard of living improves, chronic diseases and end-stage organ failure have become normal. Organ transplantation has become one of the hopes in the fight against chronic diseases and end-stage organ failure. However, the lack of sufficient organ transplants to meet the existing demand has led to a major organ shortage crisis. Researchers have turned to pigs as their target. Pigs have many advantages as xenograft donors, but direct transplantation of porcine organs to humans faces many obstacles, such as hyperacute rejection, acute humoral xenograft rejection, and coagulation dysregulation. inflammatory response, and coagulation dysregulation, endogenous porcine retroviral infection etc. Many transgenic strategies have been developed to overcome these obstacles. This review provides an overview of current advance of genetically modified pigs in xenotransplantation. Future genetic engineering-based delivery of safe and effective organs and tissues for xenotransplantation remains our goal.